Intensive Behavior Therapy for Tics and Co-Occurring ADHD: A Case Report. Issue 3 (August 2022) - Dale, Chelsea; Ramos, Marcela; Parent, Justin
Highlights: Access to trained providers in the first-line interventions for tic (CBIT) is often limited and does not explicitly address ADHD. A specialized protocol was developed adapting standard CBIT and Behavioral Parent Training (BPT) to address tics and ADHD. This case study provides preliminary evidence for an intensive combined approach to reduce tic and ADHD symptoms. Abstract: Tic disorders (TDs) can substantially impact daily child functioning across social, familial, and academic domains, leading to a significant public health impact. Additionally, an overwhelming majority of children with a TD have at least one co-occurring disorder. In particular, over 60% of children with a TD also meet criteria for attention-deficit/hyperactivity disorder (ADHD). Comprehensive Behavioral Intervention for Tics (CBIT) is a first-line treatment for youth with TDs and has been shown to be effective in reducing the frequency, duration, and severity of tics in children and adolescents. Nonetheless, access to trained CBIT providers remains limited, and common comorbid conditions are not addressed in standard CBIT. Thus, there is a need for CBIT interventions that can incorporate treatment strategies for TDs and common comorbidities. To address the critical need to address TD and common comorbidities simultaneously, the current case study presents and evaluates a 2-week intensive approach to address tic and ADHD symptoms concurrently in a peripubertal male. The child's parents reported significant improvements in tic and ADHD symptoms following the end of treatment, which were maintained throughout three follow-up booster sessions. Clinical implications and future directions to modify and improve the proposed treatment are discussed.